2012
DOI: 10.1111/j.1757-7861.2012.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Research Status and Application Prospects of Digital Technology in Orthopaedics

Abstract: In the last 10 years, basic and clinical research in orthopaedics has developed rapidly. Understanding of orthopaedic disorders involves not only routine diagnosis, but also the pursuit of highly efficient and accurate three-dimensional imaging of the intra-and extra-medullary distribution, form and structure of orthopaedic disorders, thus allowing scientific evaluation of the indications for surgery, drawing up of the best surgical plan, minimization of operative trauma and the earliest possible restoration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…The common 3D display technique including VR imaging can provide a global visualization of the calcaneus [20]. Two-dimensional MPR images could show an additional perspective which could improve depiction of the subtalar joint [21,22]. Based on those images, the present study confirmed the placement of screws and divided the cases into three groups as already noted.…”
Section: Discussionsupporting
confidence: 82%
“…The common 3D display technique including VR imaging can provide a global visualization of the calcaneus [20]. Two-dimensional MPR images could show an additional perspective which could improve depiction of the subtalar joint [21,22]. Based on those images, the present study confirmed the placement of screws and divided the cases into three groups as already noted.…”
Section: Discussionsupporting
confidence: 82%
“…However, with the advent of higher precision equipment, building of micron and submicron features is on the horizon [643]. Continued development of these technologies will pave the way for their use in many reconstructive or arthroplastic procedures, including trauma [644], oral [645] , cranio-maxillofacial [646], and spinal [647] surgeries, and ultimately total joint replacement [648].…”
Section: Manufacturing Processesmentioning
confidence: 99%
“…13,14,19 Therefore, the application of CT images can be extended widely. 20 At present, the CT postprocessing technique was sufficiently accepted and used in preoperative planning of ankle fractures 21 ; however, no studies have presented the value of CT images in the postoperative assessment of ankle fractures.…”
Section: Discussionmentioning
confidence: 99%